Systemic effects of rising atmospheric vapor pressure deficit on plant physiology and productivity. (8th March 2021) - López, José; Way, Danielle A.; Sadok, Walid
Abstract: Earth is currently undergoing a global increase in atmospheric vapor pressure deficit (VPD), a trend which is expected to continue as climate warms. This phenomenon has been associated with productivity decreases in ecosystems and yield penalties in crops, with these losses attributed to photosynthetic limitations arising from decreased stomatal conductance. Such VPD increases, however, have occurred over decades, which raises the possibility that stomatal acclimation to VPD plays an important role in determining plant productivity under high VPD. Furthermore, evidence points to more far‐ranging and complex effects of elevated VPD on plant physiology, extending to the anatomical, biochemical, and developmental levels, which could vary substantially across species. Because these complex effects are typically not considered in modeling frameworks, we conducted a quantitative literature review documenting temperature‐independent VPD effects on 112 species and 59 traits and physiological variables, in order to develop an integrated and mechanistic physiological framework. We found that VPD increase reduced yield and primary productivity, an effect that was partially mediated by stomatal acclimation, and also linked with changes in leaf anatomy, nutrient, and hormonal status. The productivity decrease was also associated with negative effects on reproductive development, and changes in architecture and growth rates that could decrease the evaporative surface or minimize embolism risk. Cross‐species quantitative relationships were found between levels of VPD increase and trait responses, and we found differences across plant groups, indicating that future VPD impacts will depend on community assembly and crop functional diversity. Our analysis confirms predictions arising from the hydraulic corollary to Darcy's law, outlines a systemic physiological framework of plant responses to rising VPD, and provides recommendations for future research to better understand and mitigate VPD‐mediated climate change effects on ecosystems and agro‐systems. Abstract : Earth is undergoing a global increase in atmospheric vapor pressure deficit (VPD) resulting from "air drying, " the effects of which on ecosystems and agro‐systems are poorly understood. Based on a meta‐analysis of data from 112 plant species across 59 traits, we find that VPD increases systematically reduce crop yields and non‐crop productivity. This reduction, observed under well‐watered conditions, arises from complex effects of VPD on various processes underlying plant physiology, several of which are not taken into account in current modeling efforts. The results point to the need for more research that takes into account this complexity to mitigate future VPD effects.